KONSERVASI LINGKUNGAN DALAM PERSPEKTIF USHÛL AL-FIQH - Mudhofir Abdullah (Millah: Journal of Religious Studies, 2010)
Environmental crisis is not only a matter of ecological damage, but also a matter of moral and spiritual crisis. Some have realized that to solve these crisis, they should take a comprehensive way both ecological and spiritual as well. Syari’ah as perennial source of Islamic tenets should be explored into practical guide for Muslim around the world. Nevertheless, Syari’ah couldn’t be explored effectively without specific tool like ushûl al-fiqh. This paper will deal with the role of ushûl al-fiqh in the deconstruction and reconstruction of Syari’ah law for environmental conservation. Furthermore, I name it eco-ushûl al-fiqh as one of argument for environmental conservations on Syari’ah perspective.